Guinness World Records 2016 (United Kingdom Guinness World Records, 2017)
"Whether it's a selfie-taking monkey, a skateboarding dog or a weasel flying on a woodpecker, the world can't get enough of crazy animal stories. Guinness world records: amazing animals is the perfect opportunity to paws for thought and celebrate the incredible creatures that steal our hearts!"--
Includes index.
Keywords: Animals -- Juvenile literature; Curiosities and wonders -- Juvenile literature; World records -- Juvenile literature; Animals -- Miscellanea; World records; Animals; Curiosities and wonders; World records